2005
DOI: 10.1254/jphs.cr0050014
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Roles of Amyloidogenic Carboxy-Terminal Fragments of the β-Amyloid Precursor Protein in Alzheimer’s Disease

Abstract: Abstract. Several lines of evidence suggest that some of the neurotoxicity in Alzheimer's disease (AD) is attributed to proteolytic fragments of amyloid precursor protein (APP) and bamyloid (Ab) may not be the sole active component involved in the pathogenesis of AD. The potential effects of other cleavage products of APP need to be explored. The CTFs, carboxyterminal fragments of APP, have been found in AD patients' brain and reported to exhibit much higher neurotoxicity in a variety of preparations than Ab. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 99 publications
1
46
0
Order By: Relevance
“…S2), confirming that LXR agonists do not alter APP abundance. Previous studies have demonstrated that carboxyl-terminal fragments (CTF) of APP impair calcium homeostasis and learning and memory and are an important toxic component in the neuropathy of AD (38). Intriguingly, we observed a trend toward increased CTF␣ and CTF␤ levels only in the hippocampus of mice treated with 33 mg/kg/day of GW3965 (supplemental Fig.…”
Section: Gw3965 Increases Abca1 and Apoe Protein Levels In A Dose-depmentioning
confidence: 49%
“…S2), confirming that LXR agonists do not alter APP abundance. Previous studies have demonstrated that carboxyl-terminal fragments (CTF) of APP impair calcium homeostasis and learning and memory and are an important toxic component in the neuropathy of AD (38). Intriguingly, we observed a trend toward increased CTF␣ and CTF␤ levels only in the hippocampus of mice treated with 33 mg/kg/day of GW3965 (supplemental Fig.…”
Section: Gw3965 Increases Abca1 and Apoe Protein Levels In A Dose-depmentioning
confidence: 49%
“…Because APP CTFs impair Ca 2ϩ homeostasis, long-term potentiation, and inflammatory processes (Yankner et al, 1989;Berger-Sweeney et al, 1999;Lahiri et al, 2002;Chang and Suh, 2005), their accumulation could contribute to neuronal dysfunction in AD. Indeed, mice with PS deficiency in forebrain neurons show age-dependent accumulation of APP CTFs and neurodegeneration (Herms et al, 2003;Saura et al, 2004), which because of the lack of ␥-secretase could not be attributed to toxic effects of A␤.…”
Section: Discussionmentioning
confidence: 99%
“…Overproduced non‐Aβ APP fragments may interact unphysiologically with cellular proteins (Chang & Suh, 2005; Mitani et al , 2012; Nicolas & Hassan, 2014; Kerridge et al , 2015; Nhan et al , 2015; Willem et al , 2015; Xia et al , 2016). See Fig 3.…”
Section: Limitations Of First‐generation Mouse Modelsmentioning
confidence: 99%